PENGGUNAAN TENAGA KERJA ASING TERHADAP PERLINDUNGAN HAK ATAS PEKERJAAN BAGI PEKERJA INDONESIA - Faisal, Muhammad; Gettari, Trie Rahmi (Ensiklopedia Sosial Review, 2025)
Abstract: Article 27 paragraph (2) of the Republic of Indonesia Constitution states that citizens have the right to work and a decent living for humanity, means that the state is obliged and responsible for providing employment for citizens to meet their living needs. Law Number 13 of 2003 concerning Manpower is the basis for protection for citizens in terms of employment. The Manpower Law also provides opportunities for employers to employ Foreign Labours. The use of foreign labours was initially aimed at transferring knowledge and technology, but with the demands of cooperation with other countries, the use of foreign labours is also for investment purposes. Article 81 of Law Number 6 of 2023 concerning Job Creation makes changes to the regulations regarding the use of Foreign Workers in Law Number 13 of 2003 concerning Manpower, by streamlining procedures. Procedural convenience and clarity regarding restrictions on the use of Foreign Labours will increase competition in obtaining jobs for Indonesian labours, This is also accompanied by increasing unemployment and workforce figures every year. So the use of foreign workers is returned to the main objective, namely the transfer of knowledge and technology.Keywords: Foreign Labour, Protection, Right to Work.